What influences consumers’ online medication purchase intentions and behavior? A scoping review - Limbu, Yam B.; Huhmann, Bruce A. (Frontiers in Pharmacology, 2024)
Objective: Consumers increasingly buy pharmaceuticals online. No scoping review has been carried out to summarize and synthesize the studies that have identified drivers of consumers’ purchase intention and behavior from online pharmacies. Thus, we conducted a scoping review to explore the extent to which prior research has studied consumer purchase intentions and behavior related to online pharmacies, the drivers previously identified to explain consumers’ online pharmacy purchase intentions and behavior, and how these antecedents differ between OTC and prescription medications. Then, we identified gaps in the published literature to form a comprehensive theory-based agenda for future research. Methods: We searched PubMed, Web of Science, and Scopus to retrieve relevant studies published in English in peer-reviewed journals. The search strategy identified forty-eight eligible studies. Results: We identified twelve types of factors influencing purchase intentions and behaviors from online pharmacies: demographics, convenience, availability, price, evaluations of the purchase environment, information sources, internet usage, prior experience, perceived risk, health insurance, privacy, and product. Our analysis also revealed differences between OTC and prescription medications in drivers of purchase intentions and behaviors. Conclusion: While demographic factors tended to be the most often measured influences on intentions and behavior, their role was generally inconsistent, with many contradictory results. However, other factors (e.g., convenience, availability, lower prices, and favorable evaluations toward the purchase environment) more consistently enhanced online medication purchase intentions and behavior. An extensive agenda for future research is advanced.